Physical activity reduces hippocampal atrophy in elders at genetic risk for Alzheimer's disease - Smith, J. Carson; Nielson, Kristy A.; Woodard, John L.; Seidenberg, Michael; Durgerian, Sally; Hazlett, Kathleen E.; Figueroa, Christina M.; Kandah, Cassandra C.; Kay, Christina D.; Matthews, Monica A.; Rao, Stephen M. (Frontiers in Aging Neuroscience, 2014)
We examined the impact of physical activity (PA) on longitudinal change in hippocampal volume in cognitively intact older adults at varying genetic risk for the sporadic form of Alzheimer’s disease (AD). Hippocampal volume was measured from structural magnetic resonance imaging (MRI) scans administered at baseline and at an 18-month follow-up in 97 healthy, cognitively intact older adults. Participants were classified as High or Low PA based on a self-report questionnaire of frequency and intensity of exercise. Risk status was defined by the presence or absence of the apolipoprotein E-epsilon 4 (APOE-ε4) allele. Four subgroups were studied: Low Risk/High PA (n = 24), Low Risk/Low PA (n = 34), High Risk/High PA (n = 22), and High Risk/Low PA (n = 17). Over the 18 month follow-up interval, hippocampal volume decreased by 3% in the High Risk/Low PA group, but remained stable in the three remaining groups. No main effects or interactions between genetic risk and PA were observed in control brain regions, including the caudate, amygdala, thalamus, precentral gyrus, caudal middle frontal gyrus, cortical white matter, and total grey matter. These findings suggest that PA may help to preserve hippocampal volume in individuals at increased genetic risk for AD. The protective effects of PA on hippocampal atrophy were not observed in individuals at low risk for AD. These data suggest that individuals at genetic risk for AD should be targeted for increased levels of PA as a means of reducing atrophy in a brain region critical for the formation of episodic memories.